2015
DOI: 10.3390/nu7125524
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products: Link between Diet and Ovulatory Dysfunction in PCOS?

Abstract: PCOS is the most common cause of anovulation in reproductive-aged women with 70% experiencing ovulatory problems. Advanced glycation end products are highly reactive molecules that are formed by non-enzymatic reactions of sugars with proteins, nucleic acids and lipids. AGEs are also present in a variety of diet where substantial increase in AGEs can result due to thermal processing and modifications of food. Elevation in bodily AGEs, produced endogenously or absorbed exogenously from high-AGE diets, is further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 107 publications
(153 reference statements)
0
16
0
1
Order By: Relevance
“…PCOS is the most common cause of anovulation in reproductive-aged women [2] and has been associated with different adverse outcomes in women undergoing assisted reproduction, such as low fertilization rate, low number of good quality embryos, and high spontaneous abortion rates after ovulation induction and after in vitro fertilization (IVF) treatments [3][4][5]. Advanced glycation end products (AGEs) are highly reactive pro-inflammatory molecules that are physiologically formed by non-enzymatic alteration of proteins, lipids, and nucleic acids by glucose or by ingestion of a variety of fast foods [6,7]. AGEs constitute a heterogeneous group of compounds of more than 20 members.…”
Section: Introductionmentioning
confidence: 99%
“…PCOS is the most common cause of anovulation in reproductive-aged women [2] and has been associated with different adverse outcomes in women undergoing assisted reproduction, such as low fertilization rate, low number of good quality embryos, and high spontaneous abortion rates after ovulation induction and after in vitro fertilization (IVF) treatments [3][4][5]. Advanced glycation end products (AGEs) are highly reactive pro-inflammatory molecules that are physiologically formed by non-enzymatic alteration of proteins, lipids, and nucleic acids by glucose or by ingestion of a variety of fast foods [6,7]. AGEs constitute a heterogeneous group of compounds of more than 20 members.…”
Section: Introductionmentioning
confidence: 99%
“…These studies substantiate the association between AGEs and hyperandrogenism in PCOS. Accumulating evidence has demonstrated that dietary modification with intake of diet containing low AGEs can reduce the concentration of plasma bioavailable testosterone and can modify PCOS phenotypes [ 21 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…AGEs, also called “glycotoxins,” are the byproducts of Maillard reaction in which the carbonyl group of carbohydrates non-enzymatically interacts with lipids or with the amino group in proteins [ 20 ]. AGEs can be formed endogenously by the body or absorbed exogenously by intake of diet containing high levels of AGEs (such as fast-food diet) or by smoking [ 21 ]. AGEs are known to play a role in the pathogenesis of different diseases such as diabetes, aging, Alzheimer disease, atherosclerosis, renal disease, and recently PCOS by causing oxidative stress, altering enzymatic activities, affecting cytotoxic pathways, or damaging nucleic acids [ 19 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…AGEs have also been shown to disrupt oocyte development, growth, and maturation in preovulatory follicles, likely via the ERK1/MAPK signaling pathways (107,108). Chronic inflammation and increased oxidative stress (53) are considered the link between mechanisms via which AGEs are linked with reproductive consequences of PCOS.…”
Section: Environmental Factors and Hormonal Disruptionmentioning
confidence: 99%